Relationship Between COVID-19, Euthanasia and Old Age: A Study from a Legal-Ethical Perspective - Salinas Mengual, Jorge (Journal of religion and health, 2021)
The global pandemic situation created by COVID-19 leaves many questions open in areas as diverse as politics, economics, society and ethics. The scarcity of health resources and the use that has been made of these by some governments raises the question of whether the distribution of health resources has been equitable, or whether the allocation of health resources depended on criteria such as age. The present work investigates whether those countries or geographical areas where euthanasia is legalized, decriminalized or socially accepted, have followed selective policies limiting access to healthcare by the elderly, thus undermining what is understood as quality of life.